Resilient reads on The Horse and His Boy by C.S. Lewis - Carreira Zafra, Cintia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article examines the key to resilience in the story of the main character of the novel by C.S. Lewis. His life experiences show the many ways a person can experience a radical change and have a resilient attitude. The objectives of our literary analysis are several. Define and update the concept of resilience, highlight the functioning of the Aristotelian theory of mimesis and metanoia, and analyse the resilient process of the literary character. All in all, it is concluded that the novel is a paradigmatic example of a resilient story and character.